The effects of maternal-child nursing clinical practicum using virtual reality on nursing students' competencies: a systematic review - Sungwoo Hwang; Hyun Kyoung Kim (Korean Society of Women Health Nursing, 2022)
Purpose This study aimed to investigate the effects of virtual reality used in maternal-child nursing clinical practicums on nursing students' competencies through a systematic review. Methods The inclusion criteria were peer-reviewed papers in English or Korean presenting analytic studies of maternal-child nursing practicums using virtual reality. An electronic literature search of the Cochrane Library, CINAHL, EMBASE, ERIC, PubMed, and Research Information Sharing System databases was performed using combinations of the keywords "nursing student," "virtual reality," "augmented reality," "mixed reality," and "virtual simulation" from February 4 to 15, 2022. Quality appraisal was performed using the RoB 2 and ROBINS-I tools for randomized controlled trials (RCTs) and non-RCTs, respectively. Results Of the seven articles identified, the RCT study (n=1) was deemed to have a high risk of bias, with some items indeterminable due to a lack of reported details. Most of the non-RCT studies (n=6) had a moderate or serious risk of bias related to selection and measurement issues. Clinical education using virtual reality had positive effects on knowledge, skills, satisfaction, self-efficacy, and needs improvement; however, it did not affect critical thinking or self-directed learning. Conclusion This study demonstrated that using virtual reality for maternal-child nursing clinical practicums had educational effects on a variety of students' competencies. Considering the challenges of providing direct care in clinical practicums, virtual reality can be a viable tool that supplements maternal-child nursing experience. Greater rigor and fuller reporting of study details are required for future research.